Metropolitan region policies in the European Union: following national, European or neoliberal agendas?. Issue 1 (2nd January 2017) - Lang, Thilo; Török, Ibolya
ABSTRACT: The paper depicts the emergence of metropolitan region policies in Europe as being linked to the globalization debate and demonstrates how the idea of supporting metropolitan regions as national growth engines appeared to become not only an element of European regional policy but has appeared more and more in national urban policies as well. We propose to regard the diffusion of the underlying spatial development ideas as being linked to Europeanization processes as a form of transnational socialization and learning. We demonstrate how the urban dimension has been more and more strengthened in EU regional policies since the early 1990s and how influential some national level policies might have been for the European level. Some new member states show recent shifts towards more neoliberal development models arguing for more competitiveness through metropolization. We propose that this interrelates to a general shift towards the paradigm of a regional policy based on growth potentials and competitiveness across the EU. While the cohesion objective is nevertheless maintained, there seems to be a widespread consensus among policy-makers in Europe that to a certain extent the metropolitan paradigm is a logical and unavoidable result of economic transformation and globalization and is needed to achieve overall competitiveness.